2016
DOI: 10.1515/frp-2016-0007
|View full text |Cite
|
Sign up to set email alerts
|

The change in weight and surface temperature of a pine cone (Pinus sylvestris L.) as a result of microwave irradiation

Abstract: In this article, the author investigates the change of weight and temperature of pine cones in a microwave oven over the following range of microwave irradiation power (PMF): 800, 620, 440, 260 and 130 W. Cones were divided into groups according to their weight and the author examined the influence of PMF on their water content and drying rate. The process is described with the help of mathematical equations and curves. The cones were irradiated in the microwave until all cones of the given group began to open… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 8 publications
(5 reference statements)
0
9
0
Order By: Relevance
“…Statistics of the physical parameters of the cones used in the study are presented in Table 2. The physical characteristics of the study material were found to be within the typical range for Europe, where the length of Scots pine cones ranges from 19 to 70 mm, their thickness ranges from 12 to 35 mm [33,34], and their weight ranges from 5 to 18.4 g [1,35]. The mean moisture content was 34%.…”
Section: Physical Characteristics Of Scots Pine Conesmentioning
confidence: 95%
See 4 more Smart Citations
“…Statistics of the physical parameters of the cones used in the study are presented in Table 2. The physical characteristics of the study material were found to be within the typical range for Europe, where the length of Scots pine cones ranges from 19 to 70 mm, their thickness ranges from 12 to 35 mm [33,34], and their weight ranges from 5 to 18.4 g [1,35]. The mean moisture content was 34%.…”
Section: Physical Characteristics Of Scots Pine Conesmentioning
confidence: 95%
“…Due to the high processing capacity that these facilities require, the need for regular deliveries of large amounts of cones is high in order to reduce extraction costs. However, this is often not easy to achieve as the availability of cone crops depends on seed years [1]. The most widespread forest tree in Central and Eastern Europe is Scots pine (Pinus sylvestris L.), hence the seed material of this species is typically used for studies.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations